Were we terrorists? History, terrorism, and the French Resistance - Millington, Chris ca. 20./21. Jh. (History compass, 2018)
This article argues that scholars of historical terrorism should abandon the practice of defining the phenomenon in favour of prioritising past understandings of terrorist violence. Research into the history of terrorism often uses a definition informed by contemporary concerns to reveal previous incidents and outbreaks of terrorism. This approach speaks more to the concerns of the present than those of the past. We must refocus our attention on how people in history understood terrorism and to whom and to what they applied the term. This approach can open avenues of investigation into neglected or sensitive subjects, with the example of the violence of the French Resistance explored here. Historians have rejected the use of the term "terrorism" to describe resistance action, preferring instead to use military or paramilitary terminology. However, resistance violence was understood in several ways, and the resisters' own rejection of the terrorist label was not total.